2018
DOI: 10.1016/j.jenvman.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

‘Too-much-of-a-good-thing’? The role of advanced eco-learning and contingency factors on the relationship between corporate environmental and financial performance

Abstract: Inspired by the natural-resource-based view (NRBV) theory, we attempt to shed light on a controversy which has been persistent over the last decade, concerning the relationship between corporate environmental performance (CEP) and corporate financial performance (CFP). Using the 'too-much-of-a-good-thing' (TMGT) concept, which suggests that "too much can be worse than too little," we link mixed results and consider the roles of advanced eco-learning and contingency factors in influencing the CEP-CFP relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 75 publications
(191 reference statements)
5
38
0
1
Order By: Relevance
“…An HTMT value of < 0.90 between constructs indicates good discriminant validity (Benitez et al, 2019;Latan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An HTMT value of < 0.90 between constructs indicates good discriminant validity (Benitez et al, 2019;Latan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several studies found a positive relationship between environmental outcomes and firm performance (Li and Ramathan, 2018;Journeault, 2016;Ambec and Lanoie, 2008;Russo and Fouts, 1997;Waddock and Graves, 1997). Nevertheless, other investigations described these relationships as nonsignificant (Al-Tuwaijri et al, 2004;Henri and Journeault, 2010;Wagner, 2015) or even negative (Qi et al, 2014;Tan et al, 2017;Vastola et al, 2017;Latan et al, 2018). For this reason, it is our intention to confirm whether a positive relationship exists between environmental outcomes and firm performance, additionally focusing on the extent to which the variables GHRM and environmental outcomes act as play a mediating role in the relationship between CSR and firm performance.…”
Section: Introductionmentioning
confidence: 98%
“…In consequence, green culture is an important strategic determinant for green innovation and for gaining a competitive advantage [14]. In recent years, different studies have been conducted on green practices, in which a competitive advantage has been gained through green culture at the organizational level, green human resources practices [15], environmental capabilities [16], environmental performance, green supply chains [17], green intellectual capital [18], ecological learning [19], innovative performance and green products, strategies for green innovation, green value chains, green human resources management, and green information system infrastructure [20,21]. This indicates that a growing consciousness surrounding green practices has been observed in companies and businesses.…”
Section: Introductionmentioning
confidence: 99%